Assessment of Glutathione Level in Non-Alcoholic Fatty Liver Disease Patients (Academia Journal of Medicine, 2020)
Background: Non-alcoholic fatty liver disease (NAFLD) is a range of hepatic disorders associated with fatty deposits in liver, which occur in the absence of alcohol consumption or alcohol abuse. NAFLD. The present study assessed glutathione level in non-alcoholic fatty liver disease patients. Subjects and Methods: The present study was conducted in Department of Internal Medicine, Narayana Medical College & Hospital, Chintareddy Palem, Nellore, Andhra Pradesh. Duration of the study was from February 2018 to January 2019. 40 patients of NAFLD and 20 cases of fatty liver disease were recruited. Serum levels of 8-OHdG were measured using the highly sensitive 8-OHdG Check enzyme-linked immunosorbent assay (ELISA). Serum levels of GGT were measured using the Qualigent® GGT kit. Serum levels of glutathione (GSH) were measured using the GSH kit. Results: The mean total bilirubin in group I was 1.2 mg/dL and in group II was 0.7 mg/dL, aspartate transaminase was 58.2 U/l in group I and 62.6 U/l in group II, alanine transaminase in group I was 142.4 U/l in group I and 128.2 U/l in group II, alkaline phosphatase was 284.2 U/l in group I and 302.4 U/l in group II and γ-glutamyltranspeptidase in group I was 98.2 U/l and 118.4 U/l in group II. The difference was non- significant (P> 0.05). The mean glutathione level in group I was 0.6 and in group II was 0.4 and which increased to 1.4 in group I and 1.2 in group II after 3 months. The difference within the group found to be significant (P< 0.05). Conclusion: Authors found that there was reduction in alanine transaminase, glutathione and gamma-glutamyltranspeptidase level. Antioxidant therapy with glutathione may reduce the pathological oxidative stress in the liver in NASH, preventing the progression from NAFLD to NASH cases.
Keywords: Alanine Transaminase; Fatty Liver; Glutathione